Konstruksi Messianisme Jamaah An-Nadzir di Kabupaten Gowa, Sulawesi Selatan - Imran Imran (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2017)
Abstract This study aims to explore primary aspects of the messianistic movement of Jamaah an-Nadzir in South Sulawesi. These aspects include how the messianistic ideology of this organization is formulated and practiced, and how they distinguish the movement from other similar messianistic movements elsewhere. This study is intended more as a cultural, rather than theological, study. Therefore, it is beyond the objective of this study to support or negate certain theological claims regarding the issue in question. Messianism in this study will be, thus, viewed from the perspective of the invention of tradition to explore the extent to which the idea of an-Nadzir’s messianism has come as a creation and to uncover the power-relation discourses in various constructions of messianism. Members of Jamaah an-Nadzir believe and claim that they are preparing themselves for the coming of the messiah of Islam, Imam Mahdi. However, they appear to develop a construction of messianism, which is different from those of other Islamic organizations. The Imam Mahdi concept advocated by this religious group is contextualized within an array of local stories. It is, for example, strongly connected to a prominent local figure of Kahar Muzakkar and the founding father of the organization, Kyai Samsuri Abdul Madjid.Keywords: Religious Movement, Messianism, Construction, Invention, Knowledge Relation. الخلاصة تهدف هذه الدراسة إلى تحليل بناء المسيحية في الجماعة النذير من خلال النظر في عدة جوانب مثل كيفية صياغة الأيديولوجية المسيحية وتنفيذها والجوانب التي تميزه عن الحركات الدينية مع الأساليب المسيحية الأخرى. هذه الدراسة الثقافية، وليس دراسة لاهوتية. هذا البحث ليس في وضع يسمح له بدعم أو إبطال بعض الادعاءات اللاهوتية. فينظر إلى المسيحية في هذه الدراسة من نظر اختراع التقليد لاستكشاف مدى فكرة مسيحية النذير الذي يأتي كابداعات ويبحث علاقات المعرفة في مختلف انشاءات المسيانية. ويعتقد مجتمع النذير ويدعي أنه يستعد لوصول المسيح الإسلامي يعنى الإمام المهدي. ومع ذلك، يبدو أنها تطور بناء المسيانية التي تختلف عن المنظمات الإسلامية الأخرى، فإنها تضيف عناصر السرد المحلية، مثل ربط شخصية الإمام المهدي مع قهار مذكر ومؤسس المجتمع، كياي سامسوري عبد المجيد.الكلمة الدالة: النذير ،الحركة الدينية، المسيانية/ المسيحية، البناء، الخلق، الخطاب العلاقة / السلطة. Abstrak Penelitian ini bertujuan untuk menganalisis konstruksi messianisme dalam Jamaah an-Nadzir dengan melihat beberapa aspek seperti bagaimana ideologi messianistik tersebut dirumuskan dan dijalankan serta aspek-aspek yang membedakannya dengan gerakan-gerakan keagamaan dengan corak messianistik lainnya. Penelitian ini merupakan sebuah penelitian kajian budaya, dan bukan kajian teologis. Penelitian ini tidak dalam posisi untuk mendukung atau menegasikan klaim teologis tertentu. Messianisme dalam penelitian ini dipandang dari perspektif invention of tradition untuk menelusuri sejauh mana gagasan messianisme an-Nadzir hadir sebagai sebuah kreasi dan menelusuri relasi kuasa pengetahuan dalam berbagai konstruksi messianisme. Komunitas an-Nadzir meyakini dan mengklaim bahwa mereka sedang mempersiapkan kedatangan sosok mesias Islam, Imam Mahdi. Uniknya, mereka menambahkan unsur narasi lokal, seperti menghubungan sosok Imam Mahdi dengan Kahar Muzakkar dan pendiri komunitas, Kyai Samsuri Abdul Madjid.Kata kunci; Gerakan Keagamaan, Messianisme, Konstruksi, Kreasi, Relasi Wacana/Kekuasaan.